Neither molecular nor morphological data have all the answers; with an example from Macrobrachium (Decapoda: Palaemonidae) from Australia - Page, Timothy J.; Hughes, Jane M. (Zootaxa, 2011)
Much controversy still seems to surround the role of molecular data in general, and DNA barcoding in particular, within the taxonomic community. This has lead to numerous “call and response” pairs of papers, most recently Ebach (2011) and Mitchell (2011), but preceded by many other pairs, such as Packer et al. (2009) and Hołyński (2010). There have been numerous calls for a more “integrative” approach to taxonomy (Mitchell 2011; Stevens et al. 2011), which itself has generated point and counterpoint papers (Dayrat 2005; Valdecasas et al. 2008). This of course is how science progresses (although Max Planck suggested that science advances “one funeral at a time”, en.wikiquote.org/wiki/Max_Planck, accessed 20 March 2011).